Agile Governance in Optimizing Digital Literacy for MSMEs Actors in the Special Region of Yogyakarta - Muhammad Eko Atmojo; Awang Darumurti; Helen Dian Fridayani; Sanny Nofrima; Herdin Saputra (Journal of Government and Civil Society, 2024)
This study aims to evaluate the effectiveness of the Yogyakarta Government's initiatives in enhancing digital literacy among Micro, Small, and Medium Enterprises (MSMEs) as a means to foster Agile Governance. The importance of improving digital literacy for MSME owners is underscored by its potential to drive economic growth in the Special Region of Yogyakarta. Employing a qualitative research methodology with a case study approach, this research highlights the critical role that MSME owners play in stimulating local economic development. The findings indicate that the Yogyakarta Government must adopt a more proactive stance in implementing Agile Governance through comprehensive digital literacy empowerment programs for MSMEs. Notably, digital marketing training has been initiated based on MSME data available on the Sibakul platform. However, challenges persist, as not all MSME owners are registered on this platform, limiting the program's reach. Additionally, the Yogyakarta Government must enhance the digital capabilities of its bureaucracy to effectively support the development of digital platforms. Addressing both external challenges—such as MSME enthusiasm and infrastructure growth—and internal challenges—like the enhancement of bureaucratic digital skills—is essential for the Yogyakarta Government to realize Agile Governance in its operational framework. This research contributes to the understanding of how digital literacy initiatives can serve as a catalyst for sustainable economic development in local governance contexts. Penelitian ini bertujuan untuk mengevaluasi efektivitas inisiatif Pemerintah Yogyakarta dalam meningkatkan literasi digital di kalangan Usaha Mikro, Kecil, dan Menengah (UMKM) sebagai upaya untuk mendorong Tata Kelola Agil. Pentingnya meningkatkan literasi digital bagi pemilik UMKM ditekankan oleh potensinya untuk mendorong pertumbuhan ekonomi di Daerah Istimewa Yogyakarta. Menggunakan metodologi penelitian kualitatif dengan pendekatan studi kasus, penelitian ini menyoroti peran penting pemilik UMKM dalam merangsang pengembangan ekonomi lokal. Temuan menunjukkan bahwa Pemerintah Yogyakarta harus mengambil sikap yang lebih proaktif dalam menerapkan Tata Kelola Agil melalui program pemberdayaan literasi digital yang komprehensif bagi UMKM. Secara khusus, pelatihan pemasaran digital telah dimulai berdasarkan data UMKM yang tersedia di platform Sibakul. Namun, tantangan masih ada, karena tidak semua pemilik UMKM terdaftar di platform ini, yang membatasi jangkauan program tersebut. Selain itu, Pemerintah Yogyakarta harus meningkatkan kemampuan digital aparaturnya untuk mendukung pengembangan platform digital secara efektif. Mengatasi tantangan eksternal—seperti antusiasme UMKM dan pertumbuhan infrastruktur—serta tantangan internal—seperti peningkatan keterampilan digital birokrasi—adalah penting bagi Pemerintah Yogyakarta untuk mewujudkan Tata Kelola Agil dalam kerangka operasionalnya. Penelitian ini berkontribusi pada pemahaman tentang bagaimana inisiatif literasi digital dapat menjadi katalisator untuk pengembangan ekonomi yang berkelanjutan dalam konteks pemerintahan lokal.